2009
DOI: 10.1080/14999011003635514
|View full text |Cite
|
Sign up to set email alerts
|

Are Measures of Cognitive Effort and Motivation Useful in Differentiating Feigned from Genuine Psychiatric Symptoms?

Abstract: This study examined the accuracy of two measures of cognitive effort and motivation, the Test of Memory Malingering (TOMM; Tombaugh, 1996) and the Validity Indicator Profile Verbal subtest (VIP-V; Frederick, 2003) using a simulation study design with psychiatric patients (n = 88) and community participants instructed to feign mental illness (n = 29). Little research has evaluated either the TOMM or the VIP in psychiatric patients, a group that may be at an increased risk of misclassification, despite the commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
(23 reference statements)
1
8
1
Order By: Relevance
“…Use of multiple measurements increases validity of these determinations, as is typically done when using free-standing effort measures like the Word Memory test that include several subscales to determine effort test failure. The 16.1% two-test failure rate is comparable to the majority of prior studies examining cognitive effort in SZ (Arnold et al, 2005;Avery et al, 2009;Back et al, 1996;Duncan, 2005;Egeland et al, 2003;Gierok et al, 2005;Moore et al, 2013;Morra et al, 2015;Pivovarova et al, 2009;Schroeder and Marshall, 2011), which suggests that the majority of outpatients with a psychotic disorder put forth adequate effort during neuropsychological testing conducted in the context of a research study. The finding that 32.1% of SZ failed at least 1 effort test calls into question what the true rate of effort test failure is in SZ.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Use of multiple measurements increases validity of these determinations, as is typically done when using free-standing effort measures like the Word Memory test that include several subscales to determine effort test failure. The 16.1% two-test failure rate is comparable to the majority of prior studies examining cognitive effort in SZ (Arnold et al, 2005;Avery et al, 2009;Back et al, 1996;Duncan, 2005;Egeland et al, 2003;Gierok et al, 2005;Moore et al, 2013;Morra et al, 2015;Pivovarova et al, 2009;Schroeder and Marshall, 2011), which suggests that the majority of outpatients with a psychotic disorder put forth adequate effort during neuropsychological testing conducted in the context of a research study. The finding that 32.1% of SZ failed at least 1 effort test calls into question what the true rate of effort test failure is in SZ.…”
Section: Discussionsupporting
confidence: 72%
“…When these measures have been applied to study insufficient effort in SZ, inconsistent rates of effort test failure have been observed. The majority of studies have indicated that approximately 15e25% of SZ patients fall below standard clinical cut-offs for low effort (Avery et al, 2009;Back et al, 1996;Duncan, 2005;Egeland et al, 2003;Gierok et al, 2005;Hunt et al, 2014;Moore et al, 2013;Pivovarova et al, 2009;Schroeder and Marshall, 2011) although a few studies report failure rates as high as 60%e72% (Gorissen et al, 2005;Hunt et al, 2014). Several factors may contribute to discrepant rates of effort test failure observed across studies, including inpatient versus outpatient status, level of personal and parental education, symptom severity, the sensitivity and specificity of effort tests administered, and whether the effort test used was embedded or freestanding (see Gorissen et al, 2005;Hunt et al, 2014;Morra et al, 2015;Strauss et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The TOMM is commonly employed and widely accepted as a measure of effort in current clinical practice. The TOMM has been found to have high specificity, although the sensitivity of this measure has varied across studies (Gervais et al, 2004;Green, 2011;Iverson et al, 2010;Merten et al, 2007;Pivovarova et al, 2009;Rees et al, 1998;Teicher & Wagner, 2004;Tombaugh, 1996Tombaugh, , 1997. Sharland and Gfeller (2007), in their review of National Academy of Neuropsychologists (NAN) professional members and fellows, found that the TOMM was the most frequently used test of effort.…”
Section: Procedures and Measuresmentioning
confidence: 96%
“…Although the TOMM has been found to have a high level of specificity, there has been variability in the literature regarding the sensitivity of this measure (Gervais, Rohling, Green, & Ford, 2004;Iverson, Lange, Brooks, & Rennison, 2010;Rees et al, 1998). Specifically, in very impaired populations such as patients with severe dementia, the TOMM has been found to have a high false-positive rate, whereas in TBI samples, the falsepositive rate is low (Iverson et al, 2010;Merten et al, 2007;Pivovarova, Rosenfeld, Dole, Green, & Zapf, 2009;Rees et al, 1998;Teicher & Wagner, 2004;Tombaugh, 1996Tombaugh, , 1997. That the TOMM may have low sensitivity has been demonstrated in both clinical and undergraduate samples (An, Zakzanis, & Joordens, 2012;Armistead-Jehle & Gervais, 2011).…”
mentioning
confidence: 89%
See 1 more Smart Citation